The Project Trauma-Informed Practice for Workers in Public Service Settings: New Strategies for the Same Old Objective - Dores Artemisa R.; Letica-Crepulja Marina; Silva Regina A. (Open Education Studies)
Many professionals are confronted in their practice with clients who show post-traumatic symptoms (PTS). “Trauma-informed practice” helps professionals recognize, understand, and appropriately respond to the effects of trauma. This work presents the “Trauma-Informed Practice for Workers in Public Service Settings” – TIPS (Erasmus+). The project sought to: (1) increase awareness among professionals about the occurrence of PTS; (2) equip them with skills to identify PTS and reduce barriers related to discrimination; (3) improve the care and support provided; and (4) reflect on innovative pedagogical strategies. This was a distance learning experience aimed at professionals from various sectors, namely education. The project is based on training through new digital spaces and learning tools, combined with strategies of storytelling and teaching practices based on narrativization. The project includes the following final outputs (1) guidelines; (2) a catalog; (3) a resource pack; (4) an interactive e-platform; and (5) a mobile application. The diverse learning opportunities and formats aims to promote new and improved learning strategies, respecting personal preferences and diversity of learning styles, thus ensuring new paths to the “old” objective of effective learning.